Nuclear Material Performance - Abdel Rahman, Rehab O.; El-Din Mostafa Saleh, Hosam (IntechOpen, 2016)
Assessing and improving nuclear material performance is a crucial subject for the sustainability of the nuclear energy and radioactive isotope supplies. This book aims to present research efforts used to identify nuclear materials performances in different areas. The contributions of esteemed international experts have covered important research aspects in fission and fusion technologies and naturally occurring radioactive materials management. The authors introduced current and anticipated trends toward better performances and mitigating challenges for commercial application of innovative technologies, biological remediation of mine effluents, nuclear fuel performance in power and research fission reactors, gamma ray spectrometer calibration, and recent advances in understanding the performance of tungsten composite in fusion reactor environment.